Exterior walls selection framework using Building Information Modeling (BIM). Issue 1 (31st December 2022) - Saud, Ammar M.; Al-Gahtani, Khalid S.; Alsugair, Abdullah M.
Abstract: The building material selection among different options is a crucial issue affected by quality and cost. The implementation of the value engineering (VE) process is challenging. Thus, this paper proposes a framework for automating the VE process and integrating it with the decision-making process for building material selection. Moreover, this process becomes easily applicable by using Building Information Modelling (BIM). This study's research methodology combines VE, Analytical Hierarchy Process (AHP), Pairwise, and Function Analysis System Technique (FAST) methods to select the best choice of eight assemblies of exterior walls based on nine identified criteria. Moreover, a questionnaire is used to validate the chosen criteria weights. Furthermore, a case study of a commercial building is conducted. Eight assemblies of exterior walls are modeled and evaluated using the proposed framework. Finally, the results are presented to three experts to receive their feedback, and it shows that the proposed framework gives a reliable evaluation of the value of each alternative. The programmed framework with BIM is a great aid to the decision-maker to select the most valuable materials during the design stage. This study gives guidance to future studies to standardize the external walls alternative to be evaluated more efficiently.